Eco-Spirituality in “Sedekah Laut” Tradition: The Basis of Religious Moderation and Ecological Education in Coastal Communities - Muniroh, Siti Mumum; Ahmad, Maghfur; Huda, Miftahul; Anggraeni, Dewi; Suharto, Slamet (Edukasia Islamika : Jurnal Pendidikan Islam, 2025)
This article critically examines the meaning, values, symbols, and relationships between actors in the “Sedekah Laut” tradition as a manifestation of culturally and spiritually based environmental education. “Sedekah Laut” serves as a mitigation tool amidst the climate crisis. Through ecofeminist theory, this study integrates women, nature, and spirituality. This research positioned “Sedekah Laut” not only as a pillar of religious moderation in the cultural aspect but also as a space for ecological education that embraces gender equity. The location of this qualitative research was Wonokerto District, Pekalongan Regency. Data were obtained through interviews, observation, and documentation and analyzed using the Miles and Huberman model. The research results indicate that “Sedekah Laut” possesses ecological philosophy, meaning, and symbolism. It serves as an inclusive and adaptive instrument for addressing the climate crisis. “Sedekah Laut” serves as a space for environmental education, emphasizing women as key actors, both in the domestic and ritual spheres. This study offers a novelty in the form of a reconstruction of environmental education based on local traditions and spirituality that favors women and nature. The theoretical implications of this study expand the scope of environmental education to include spiritual-ecological aspects, while in practice, “Sedekah Laut” can serve as a model for ecological education that is inclusive, contextual, emancipatory, sustainable, and focused on climate justice.